The love script - Shiloh, Toni (Shiloh, Toni. Love in the spotlight, 2023)
"Hollywood hair stylist and makeup artist Neveah loves making those in the spotlight look their best. But when the spotlight is on her after a photo of her and Hollywood heartthrob Lamont goes viral for all the wrong reasons, they suddenly find themselves in a fake relationship to save their careers. In a world where nothing seems real, can Neveah be true to herself...and her heart?"--